A dynamic model of crisis management from a stakeholder perspective: the case of COVID-19 in China. Issue 4 (11th April 2021) - Li, Bin; Zhang, Tingting; Hua, Nan; Wang, Youcheng
Abstract : Purpose: This study aims to develop a holistic and dynamic model that governs the various relationships among the critical factors of crisis management from a stakeholder perspective in the context of China's COVID-19 epidemic outbreak. Design/methodology/approach: Data were collected from 731 textual sources, and the text mining technique identified the themes of a holistic crisis management model. Then, content analysis was applied to reveal in-depth insights into the themes. Findings: From a stakeholder perspective, the model comprises six elements: political environment, economic environment, technology, social environment, health and science and international relationships, which relate significantly to four procedural actions: prevention, response, recovery and adaptation. The overlapping stages and situational dynamic mechanisms of the process are another two new major findings of this study; learning and preparing are threaded throughout the whole dynamic process. Practical implications: Hospitality stakeholders are advised to collaborate under the guidance of the dynamic crisis management model and adopt high-technology tools for the industry's recovery management. Developing a new business model and marketing strategy is a useful approach to face similar crisis management challenges in the future. Originality/value: This paper fills an existing research gap by presenting a health-related crisis management model that can be used to evaluate the dynamic process of collaborations among stakeholders in coping with external challenges forced upon the hospitality industry. Abstract : 利益相关者视角下的危机管理动态模型：以covid-19在中国的发展为例 目的: 本研究以中国新冠肺炎疫情为背景, 从利益相关者的角度构建危机管理关键因素之间各种关系的整体动态模型。 设计/方式/方法: 本研究从731个文本来源收集定量数据, 并通过文本挖掘技术识别危机管理模型的构成要素, 并运用内容分析对构成要素进行深入剖析。 发现: 从利益相关者的角度来看, 该模型包括六个要素:政治环境、经济环境、技术、社会环境, 健康科学和国际关系。这些要素与预防、反馈、恢复和适应这四项运行程序密切相关。本研究的两大发现是防疫机制的动态机制和重叠特性, 学习和预备贯穿于疫情防控的整个动态过程。 实践意义: 酒店利益相关者应在动态危机管理模型的指导下进行合作, 并运用高科技进行行业复苏管理。此外, 开发新的商业模式和营销策略也是面对新的外部环境的有效途径。 创新/价值: 本文通过提出一个健康相关的危机管理模型来填补现有研究的空白, 该模型可用于评估酒店行业外部环境中利益相关者之间的动态合作过程。 Abstract : Objetivo: En este estudio se recogieron datos cuantitativos de 731 fuentes textuales, se identificaron los elementos constitutivos del modelo de gestión de crisis a través de la minería textual y se analizaron en profundidad los elementos constitutivos mediante el análisis de contenido. Diseño/método/enfoque: este estudio utiliza una combinación de minería de texto y análisis de contenido para explorar el manejo de crisis del brote de covid-19 en el sector turístico y hotelero de China. En primer lugar, se recogieron datos cuantitativos de 731 fuentes textuales y se identificaron los elementos constitutivos del modelo de gestión de crisis a través de la minería textual. En segundo lugar, se utiliza el análisis de contenido para analizar en profundidad los elementos constitutivos y, sobre la base de UN análisis de datos exhaustivo y una revisión de la literatura, se llega a UN marco teórico para el manejo de crisis. Encontró: Desde el punto de vista de las partes interesadas, el modelo consta de seis elementos: el entorno político, el entorno económico, el entorno tecnológico, el entorno social, la ciencia de la salud y las relaciones internacionales. Estos elementos están estrechamente relacionados con los cuatro procedimientos operativos: prevención, retroalimentación, recuperación y adaptación. Los dos principales hallazgos de este estudio son los mecanismos dinámicos y las características de superposición de los mecanismos de prevención de epidemias, y el aprendizaje y la preparación a lo largo de todo el proceso dinámico de prevención y control de brotes. Significado práctico: las partes interesadas del sector hotelero deben colaborar bajo la guía de UN modelo dinámico de gestión de crisis y utilizar la alta tecnología para la gestión de la recuperación del sector. Además, el desarrollo de nuevos modelos de negocio y estrategias de marketing es también una forma eficaz de afrontar el nuevo entorno externo. Originalidad/valor: este artículo colma las lagunas de la investigación existente proponiendo UN modelo de gestión de crisis relacionadas con la salud que pueda ser utilizado para evaluar procesos dinámicos de colaboración entre los interesados en el entorno externo del sector hotelero.